Rapid and simple analysis of amphetamine-type illegal drugs using excitation-emission matrix fluorescence coupled with parallel factor analysis - Buyi Xu; Yi Ye; Linchuan Liao (Oxford University Press, 2019)
Nowadays, the abuse of illegal drugs has been an increasingly grim problem in the world. Excitation-emission matrix fluorescence combined with parallel factor analysis was used to make a quantitative analysis of the simulated amphetamine-type illegal drugs. Satisfactory results were achieved for simultaneous determination of methamphetamine (MAM) and 3, 4-methylenedioxymethamphetamine (MDMA) in the presence of adulterants. The average recoveries were (99.8 ± 0.6)% and (101.6 ± 5.7)% for MAM and MDMA, respectively. Figures of merit including root-mean-square error of calibration and prediction, sensitivity and selectivity were investigated to evaluate the performance of the proposed method. The limits of detection were 0.054 and 0.002 1 μg/mL for MAM and MDMA, respectively.